2021
DOI: 10.1021/acs.joc.1c01385
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Transient, Carbodiimide-Induced Geometry Changes in Diphenic Acids

Abstract: Nucleotide-induced conformational changes in motor proteins are key to many important cell functions. Inspired by this biological behavior, we report a simple chemically fueled system that exhibits carbodiimide-induced geometry changes. Bridging via transient anhydride formation leads to a significant reduction of the twist about the biaryl bond of substituted diphenic acids, giving a simple molecular clamp. The kinetics are welldescribed by a simple mechanism, allowing structure−property effects to be determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[15,16] This chemistry has been applied, for example, to the generation of transient gels, [15,17,18] other assemblies, [19,20] and macrocycles, [16,21] and to the modulation of materials properties [22,23] and driving of intramolecular motion. [24,25] In previous work, [16] we showed that anhydride-based crown ethers could be generated by the action of a carbodiimides. An example is shown in Scheme 1a: when an aqueous solution of diacid TEG-Ac is treated with the carbodiimide N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), the macrocycle TEG-An is formed along with acyclic oligomers (not shown).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] This chemistry has been applied, for example, to the generation of transient gels, [15,17,18] other assemblies, [19,20] and macrocycles, [16,21] and to the modulation of materials properties [22,23] and driving of intramolecular motion. [24,25] In previous work, [16] we showed that anhydride-based crown ethers could be generated by the action of a carbodiimides. An example is shown in Scheme 1a: when an aqueous solution of diacid TEG-Ac is treated with the carbodiimide N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), the macrocycle TEG-An is formed along with acyclic oligomers (not shown).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most versatile fuel reactions is the formation of anhydrides or activated esters by the hydration of carbodiimides [15,16] . This chemistry has been applied, for example, to the generation of transient gels, [15,17,18] other assemblies, [19,20] and macrocycles, [16,21] and to the modulation of materials properties [22,23] and driving of intramolecular motion [24,25] …”
Section: Introductionmentioning
confidence: 99%
“…Thus, several chemically fueled reaction cycles have been designed to regulate molecules. The energy transduced by these cycles can come from the oxidation of reducing agents, hydrolysis of methylating agents, hydration of carbodiimides, and hydrolysis of ATP. , These cycles lead to a range of assemblies, including fibers, droplets, , vesicles, micelles, , colloids, , and particle clusters. , A well-studied cycle produces energy by hydrating carbodiimides. , In these cycles, carboxylates react with EDC (1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide) to form an O -acylurea intermediate. A second carboxylate attacks this intermediate to form the anhydride product.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the first case, a chiral, enantiopure carbodiimide is used as a fuel to drive the unidirectional motion about the single bond joining two conveniently substituted aromatic rings, namely, a 2-carboxy-phenyl group and a 2-carboxy-N-pyrrolyl group (1, Figure 1). This astonishing achievement has been made possible by previous findings concerning (i) the use of a carbodiimide (EDC) as a fuel to temporally control the conformation of the single bond between two phenyl groups, both substituted with a carboxylic function in the ortho position (2, Figure 1) by Hartley and co-workers 5 and (ii) the exploitation of the same kind of fuel to drive the motions of a rotaxane-based information ratchet by Leigh and co-workers. 6 Addition of the carbodiimide fuel to 1 or 2 induces the transient formation of an intramolecular anhydride bond, which temporarily limits the rotation about the single bond between the aromatic rings (see Figure 1, red bond in 1 and 2).…”
Section: ■ Introductionmentioning
confidence: 99%